(untitled) (Bangladesh Journal of Microbiology, 2010)
In developing countries, cervical cancer is the most common cause of cancer related to mortality in women. But the epidemiology of human papillomavirus (HPV) in different areas of Bangladesh is largely unknown both in risk groups and in the general population. The objective of the present study was to determine the risk factors associated with having HPV and the prevalence of high-risk HPV types among women with highrisk behaviour and to assess its potential impact on preventive strategies as the sex workers are at increased risk for sexually transmitted infections (STI), HPV and hence cervical cancer. Cervical swab from 293 sex workers in Dhaka City between August and September 2003 and between February 2005 and May 2006 were screened for HPV DNA using an HPV short fragment (E6) polymerase chain reaction (PCR) based assay. HPV positive samples were genotyped with nested multiplex polymerase chain reaction (NMPCR) for the highrisk types. The overall HPV prevalence in sex workers was 75.8%, whereas for the high risk type it was 49.8%. Prevalence of single genotype and multiple types of HPV was 33.1 and 16.7% respectively. The most prevalent high-risk HPV types, in order of prevalence rate, were HPV16, HPV18, HPV58, HPV45, HPV31 and HPV33. Both HPV 16 and HPV 18 were present in 21% of the cases. Targeting HPV 16 and 18 with prophylactic vaccines could possibly have an important impact on the incidence of invasive cervical carcinoma in this group of women. Primary prevention and cervical cancer screening programmes should be optimized more and run yearly among the general population. It is proposed to screen sex workers when they enter prostitution regardless of their age. Keywords: Human papillomavirus (HPV); High-risk HPV types; Cervical cancer; Sex workers DOI: http://dx.doi.org/10.3329/bjm.v25i1.4861 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 65-68